Coincident pre-diabetes is associated with dysregulated cytokine responses in pulmonary tuberculosis. - Nathella Pavan Kumar; Vaithilingam V Banurekha; Dina Nair; Rathinam Sridhar; Hardy Kornfeld; Thomas B Nutman; Subash Babu (PLoS ONE, 2014)
Cytokines play an important role in the pathogenesis of pulmonary tuberculosis (PTB)--Type 2 diabetes mellitus co-morbidity. However, the cytokine interactions that characterize PTB coincident with pre-diabetes (PDM) are not known.To identify the influence of coincident PDM on cytokine levels in PTB, we examined circulating levels of a panel of cytokines in the plasma of individuals with TB-PDM and compared them with those without PDM (TB-NDM).TB-PDM is characterized by elevated circulating levels of Type 1 (IFNγ, TNFα and IL-2), Type 17 (IL-17A and IL-17F) and other pro-inflammatory (IL-1β, IFNβ and GM-CSF) cytokines. TB-PDM is also characterized by increased systemic levels of Type 2 (IL-5) and regulatory (IL-10 and TGFβ) cytokines. Moreover, TB antigen stimulated whole blood also showed increased levels of pro-inflammatory (IFNγ, TNFα and IL-1β) cytokines as well. However, the cytokines did not exhibit any significant correlation with HbA1C levels or with bacterial burdens.Our data reveal that pre-diabetes in PTB individuals is characterized by heightened cytokine responsiveness, indicating that a balanced pro and anti - inflammatory cytokine milieu is a feature of pre-diabetes--TB co-morbidity.